The Effect Of Investment Knowledge, Social Media Influencers, And Financial Literacy On Investment Interest In The Capital Market In Students Of Management Program At Duta Bangsa University - Winarso Aji, Alpian; Suyatno, Agus; Alia Akhmad, Khabib (Jurnal Bisnis Manajemen dan Akuntansi (BISMAK), 2024)
Investment is becoming a trend that stands out in society, therefore cases of fraud or illegal investments via the internet have been increasingly happening lately, students can become victims if they do not have adequate investment knowledge, sufficient financial literacy, and good financial management. This study aims to determine the influence of investment knowledge, social media influencers and financial literacy on students' interest in investing in the capital market. The research method used is descriptive quantitative with multiple linear regression analysis. The results of this study found that investment knowledge had a positive and insignificant influence on investment intention, social media influencers and financial literacy had a positive and significant effect on investment interest. The implications of this research are for related party policy recommendations, financial education and financial product development.